Did The Crisis Strengthen Bank Competition in Indonesia?: Market Structure Analysis Pre and Post The 2008 Financial Crisis - Khoirunurrofik, Khoirunurrofik; Prabowosunu, Mohammad Alvin; Fansuri, Mohammad Ikhsan (Universitas Airlangga, 2020)
The banking industry has become a substantial part of the economy. This paper traces the change in market structure and assess the level of competition among the top 10 banks of Indonesia for the period 2005-2014. Then also distinguishing between before and after the Global Financial Crisis. Utilizing the Panzar-Rosse method and panel data, we discovered that the results show an increase in the H-value from 2005-2009 to 2010-2014 and a movement towards an almost perfectly competitive environment. Interest rates drove the short response of post-crisis on the competition. Therefore governmental supervision is required to prevent liquidity issues due to the imposition of high-interest rates. Keywords: Banking, Competition, Global Financial Crisis, Panzar-Rosse Model JEL: D40, D41, G21, L11